EVOLVE platform, a trispecific T cell engager with integrated CD2 costimulation, for the treatment of solid and hematologic tumors - Oksana A. Sergeeva; Guixian Jin; Mohosin Sarkar; Jennifer Zeiger; Sonali Dhindwal; Shu Shien Chin; Abudukadier Abulizi; Zengzu Lai; Colleen Brown; William G. DeMaria; Donal Ryan; Xingyue An; et al. (Proceedings of the National Academy of Sciences, 2025)
Ten CD3 T cell engagers (TCEs) have received regulatory approval for the treatment of hematologic and solid tumors. However, limited costimulatory signaling essential for sustained T cell effector activity may limit CD3 TCE clinical efficacy and response duration. The CD2 receptor is an attractive costimulation target owing to its association with T cell receptor signaling and favorable expression profile. We show that CD2 costimulation is superior in maintaining T cell viability and effector function relative to other pathways in in vitro chronic stimulation assays. The extracellular domain of CD58, the predominant CD2 ligand, is functional as an antibody fusion, improving bispecific potency. We observe that higher CD3 affinity molecules have the potential for superagonism in the context of an integrated CD2 agonist. Evaluation of TCEs with integrated CD2 costimulation and attenuated CD3 binding identified optimal CD3 affinity agonists that avoid target-independent T cell activation and demonstrated an increased therapeutic index relative to nonattenuated CD3 agonists. This platform shows increased tumor-killing efficacy as compared to CD3 affinity-matched bispecifics for known tumor targets such as HER2, CD20, B7-H4, and UL16-binding protein 2 (ULBP2). We demonstrate that ULBP2-targeted trispecifics with integrated CD2 costimulation and optimized CD3 affinity are superior to higher-affinity CD3 molecules in in vivo mouse efficacy studies. This integrated CD2 costimulation platform, which we termed EVOLVE, represents a next-generation TCE platform to increase T cell effector function in the tumor microenvironment and has the potential to address unmet patient needs by improving the depth and durability of clinical antitumor T cell responses.